ANALYZING THE USE OF TEXTBOOK IN MATHEMATICS EDUCATION: THE CASE OF ESTONIA - Lepik, Madis (Acta Paedagogica Vilnensia, 2015)
Textbooks are among the most powerful influences on school mathematics. In this paper, the results of the empirical study of Estonian lower secondary mathematics teachers’ approaches to the use of textbooks will be discussed. The analysis is based on the survey of 164 teachers and observation of 29 lower secondary mathematics classes. The aim is to understand the range of approaches in which textbooks are used in different mathematics classrooms. Analyses reveal that textbook serves as a central instructional tool which is in active use in Estonian mathematics classes in about half of the lesson time. At the same time, most of the teachers use the textbook simply as an exercise book. It appears that often pupils have a limited access to the textbook, and in this way textbooks are not fully used as multifaceted resources for learning pupils.
Keywords: textbook studies; lower secondary mathematics; learning outcomes; content literacy; teaching; teacher